Immigrant networks and the take-up of disability programs: Evidence from US census data - Delia Furtado; Nikolaos Theodoropoulos (Institute for the Study of Labor (IZA), 2012)
This paper examines the role of ethnic networks in disability program take-up among working-age immigrants in the United States. We find that even when controlling for country of origin and area of residence fixed effects, immigrants residing amidst a large number of co-ethnics are more likely to receive disability payments when their ethnic groups have higher take-up rates. Although this pattern can be partially explained by cross-group differences in satisfying the work history or income and asset requirements of the disability programs, we also find that social norms and, to a lesser extent, information sharing play important roles.
Keywords: C31; H55; I18; J61; 330; social security disability insurance; supplementary security income; networks; immigrants; Erwerbsunfähigkeitsrente; Migranten; Ethnische Gruppe; Soziales Netzwerk; USA